Artificial reefs built by 3D printing: Systematisation in the design, material selection and fabrication. (2nd January 2023) - Yoris-Nobile, Adrian I.; Slebi-Acevedo, Carlos J.; Lizasoain-Arteaga, Esther; Indacoechea-Vega, Irune; Blanco-Fernandez, Elena; Castro-Fresno, Daniel; Alonso-Estebanez, Alejandro; Alonso-Cañon, Sara; Real-Gutierrez, Carlos; Boukhelf, Fouad; Boutouil, Mohamed; Sebaibi, Nassim; et al.
Highlights: Artificial reefs built with 3D printing. Systematisation in the design, material selection and fabrication of artificial reefs. Sustainable materials in concrete 3D printing. Sustainable materials for artificial reefs. LCA and MCDM of concrete for 3D printing. Numerical simulations of artificial reefs. Abstract: The recovery of degraded marine coasts and the improvement of natural habitats are current issues of vital importance for the development of life, both marine and terrestrial. In this sense, the immersion of artificial reefs (ARs) in the marine environment is a way to stimulate the recovery of these damaged ecosystems. But it is necessary to have a multidisciplinary approach that analyses the materials, designs and construction process of artificial reefs in order to understand their true impact on the environment. For this reason, this paper presents the manufacture of artificial reefs by 3D printing, proposing designs with a combination of prismatic and random shapes, with different external overhangs as well as inner holes. For the definition of the artificial reef designs, criteria provided by marine biologists and the results obtained from a numerical simulation with ANSYS were taken into account, with which the stability of the artificial reefs on the seabed was analysed. Three dosages of cement mortars and three dosages of geopolymer mortars were studied as impression materials. The studies included determination of the rheological properties of the mortars, to define the printability, determination of the cost of the materials used, and determination of the mechanical strength and biological receptivity in prismatic specimens that were immersed in the sea for 3 months. To evaluate the environmental impact of the materials used in the production of the mortars, a Life Cycle Assessment (LCA) was carried out. In order to choose the mortars that encompassed the best properties studied, Multi-Criteria Decision Making (MCDM) was applied and the two best mortars were used for the manufacture of the artificial reefs. Finally, the advantages and disadvantages of the 3D printing process used were analysed. The results of the studies carried out in this research show that cement mortars have better characteristics for artificial reef applications using 3D printing, and that the technique applied for the manufacture of the artificial reefs allowed the digital models to be faithfully reproduced.